Transformaciones en el paisaje cultural de un asentamiento de origen cimarrón en la costa norte de Colombia, San Basilio de Palenque. Siglos XIX y XX: Anotaciones y reflexiones actualizadas - Mantilla Oliveros, Johana Caterina (Notas de Antropología de las Américas, 2025)
This text was published eleven years ago as a chapter for a publication in Portuguese. In it I presented an approach to the transformations that occurred in the late nineteenth and early twentieth centuries in the cultural landscape of San Basilio de Palenque, a community of Maroon origin in northern Colombia. The present text builds on the original version by replicating much of the original text, now translated into Spanish. However, in this version I have added reflections that clarify and support to a better extent the ideas originally formulated in the Portuguese version. Thus, it contains fragments of oral accounts of Palenqueros who were important to the community and who have passed away in the course of the last decade. These guided reflection on the spatial and social transformations that took place, while providing an initial context from which to begin to articulate the material culture.